2021
DOI: 10.24171/j.phrp.2021.12.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Psychological outcomes of the COVID-19 pandemic among pregnant women in Indonesia: a cross-sectional study

Abstract: Since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus first broke out in China in December 2019, it has continued to spread [1,2]. The resultant coronavirus disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
1
8
0
2
Order By: Relevance
“…It should be noted that this is a self-reported experience and validated psychological measures were not utilised in this study. However, our findings are supported by a recent cross-sectional study in Indonesia of 120 women to assess psychological outcomes during the current pandemic [ 23 ] in which the Depression, Anxiety and Stress Scale-21 (DASS-21) was administered as an online survey for pregnant women or women who had recently given birth. Similar to this study, they reported that just over half the sample had anxiety (53.3%).…”
Section: Discussionsupporting
confidence: 73%
“…It should be noted that this is a self-reported experience and validated psychological measures were not utilised in this study. However, our findings are supported by a recent cross-sectional study in Indonesia of 120 women to assess psychological outcomes during the current pandemic [ 23 ] in which the Depression, Anxiety and Stress Scale-21 (DASS-21) was administered as an online survey for pregnant women or women who had recently given birth. Similar to this study, they reported that just over half the sample had anxiety (53.3%).…”
Section: Discussionsupporting
confidence: 73%
“…] 2021 Iran 801 N/A 69 King LS [ 76. ] 2021 US 725 p < 0.001 70 Nurrizka RH [ 77. ] 2021 Indonesia 120 N/A 71 Jelly P [ 78.…”
Section: Resultsmentioning
confidence: 99%
“…] Sri Lanka 257 2020 Anxiety,Depression HADS-A, HADS-D Zeng X [ 116. ] China 516 2020 Anxiety,Depression,Sleep disorders GAD-7,EPDS, DSM-IV Nurrizka RH [ 77. ] Indonesia 36 2021 Anxiety DASS-21-A Wu Y [ 9.…”
Section: Resultsmentioning
confidence: 99%
“…Of the ten excluded studies, two papers were reviews, seven papers lacked enough data, and one paper was excluded with duplicated data [22] and the updated data were included [23]. Finally, 17 studies [1,8,12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] met the inclusion criteria for this study, including 15,050 pregnant women during the COVID-19 pandemic. The details in selected studies were listed in Table 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%